Management control systems and business performance: Evidence from Sri Lankan apparel industry - Weerathunga, Vipuli Maheshika; Seneviratne, S M Chaturika (International Journal of Financial, Accounting, and Management, 2023)
Purpose: The objective of this study is to explore the types and nature of management control practices and how they influence the business performance of two large apparel manufacturing companies in Sri Lanka. Research methodology: The research uses in-depth multiple case-study approaches based on a Sri Lankan apparel manufacturing company. Data is collected using interviews, participant observations, and documentary evidence. To achieve the objectives, thematic analysis is used as the analysis tool. Results: The findings of the study revealed that the existence of tight, strong, impactful, and effective MCSs (Management Control Systems) leads to both high sales volume and also elevates the annual growth of sales of two main apparel companies in Sri Lanka. Moreover, it is found that the effective placement and use of MCSs have a considerable influence on the profitability of the case companies. Limitations: The main limitation of this study is that it only focuses on two apparel exporting companies in the Sri Lankan apparel industry. Further, this research is a case study-based qualitative research where the inherent shortcomings of any such research are unavoidable where the personal traits of individuals as they place more significance on personal beliefs, opinions, and judgments than the results. Similarly, there is no articulated way to analyze qualitative data in an arithmetical manner. Contribution: This study contributes to the management discipline in the apparel industry in Sri Lanka and steers the Sri Lankan economy in a positive direction, as the research keeps an eye on the apparel industry at large.